2017
DOI: 10.21013/jmss.v8.n1.p7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Service Quality and Price Perception on Corporate Image, Customer Satisfaction and Customer Loyalty among Mobile Telecommunication Services Provider

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 4 publications
4
13
0
2
Order By: Relevance
“…In this case, the company's image is important for every company because it is an overall impression that is formed in the minds of the public about the company. Huang (2016) has proven that company image has a positive and significant effect on customer satisfaction, as well as other researchers, have proven that there is a significant influence between the corporate image on customer satisfaction (Ashraf et al, 2018;Dachyar & Siva, 2016;Hermawan et al, 2017;Nguyen et al, 2018), and have an impact on increasing customer loyalty (Ashraf et al, 2018;Dachyar & Siva, 2016;Huang, 2016;Sari, 2018;Xhema et al, 2018). While the findings by Variano (2017) that Brand Image has no significant effect partially on Brand Loyalty.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…In this case, the company's image is important for every company because it is an overall impression that is formed in the minds of the public about the company. Huang (2016) has proven that company image has a positive and significant effect on customer satisfaction, as well as other researchers, have proven that there is a significant influence between the corporate image on customer satisfaction (Ashraf et al, 2018;Dachyar & Siva, 2016;Hermawan et al, 2017;Nguyen et al, 2018), and have an impact on increasing customer loyalty (Ashraf et al, 2018;Dachyar & Siva, 2016;Huang, 2016;Sari, 2018;Xhema et al, 2018). While the findings by Variano (2017) that Brand Image has no significant effect partially on Brand Loyalty.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, in a study conducted by Marcos and Coelho (2017) that there is a positive and significant direct effect between service quality on customer loyalty in the insurance industry in Portugal. Whereas, other researchers found the opposite that service quality had no significant effect on customer or customer loyalty (Basir et al, 2015;Hermawan et al, 2017;Kishada & Wahab, 2015;Mandung et al, 2018;Sitorus & Yustisia, 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Previous previous research by Annas Plyriadi (2013), Ren-Fang Chao, et al (2015), Dudung Juhana, et al (2015) and Bambang Hermawan, et al (2017) also found that service quality variables had a positive and significant effect on customer satisfaction. H1: Quality of service has a positive and significant effect on patient satisfaction at hospitals in Makassar City.…”
Section: Relationship Between Service Quality and Patient Satisfactionmentioning
confidence: 73%
“…As for the relationship between service quality and customer satisfaction, many previous studies such as the one conducted by Annas Plyriadi (2013), Untung Setito Purwanto, Raihan (2017), Bambang Hermawan, et al (2017) found that service quality had a positive effect. and significant to satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Penelitian menurut (Hermawan, Basalamah, Djamereng, & Plyriadi, 2017) menyatakan bahwa persepsi harga berpengaruh positif dan signifikan terhadap kepuasan pelanggan serta (Widyasari, Soliha, Wuryan, & Damayanti, 2018) menyatakan citra merek dan kepuasan secara parsial berpengaruh positif dan signifikan terhadap loyalitas pelanggan.…”
Section: Daftar Operator Telepon Seluler DI Indonesiaunclassified